Effects of soy protein isolate on mechanical and hydrophobic properties of oxidized corn starch film - Liu, Chenglong; Yu, Bin; Tao, Haiteng; Liu, Pengfei; Zhao, Haibo; Tan, Congping; Cui, Bo (Food science & technology, 2021)
Oxidized corn starch (OS) has a good film-forming ability; however, its poor mechanical properties and moisture barrier are shortcomings. To improve the deficiencies of OS film, soy protein isolate (SPI) with different ratios (10%, 20%, and 30%) was incorporated into OS film at different pH values (6, 8, and 10) to investigate the mechanical and hydrophobic properties of the blended films. The blended films were characterized by water sensitivity, contact angle, mechanical properties, optical properties, and microstructure. The increases in the SPI ratio and pH reduced the moisture content and total soluble matter of the blended films. The reduction in water vapor permeability and the increase in contact angle from 37.3° to 104.5° suggested that the moisture barrier of the OS film was improved by SPI. The elongation at break of blended films increased, but the tensile strength decreased with increasing of SPI content and pH. The blended films prepared at pH 10 were more yellow and had higher transmittance. Scanning electron microscopy and atomic force microscopy showed that the blended films exhibited denser microstructures and smoother surfaces with the increasing pH. X-ray diffraction and thermogravimetric analysis implied that SPI interfered with the intermolecular interaction of OS. [Display omitted] •SPI reduced the tensile strength of the OS/SPI films, which was contrary to E.•The OS/SPI films had better water resistance than OS film.•The OS/SPI films presented a yellowish color and higher transmittance.•The physicochemical properties and microstructure of OS/SPI films are related to pH.